The Relationship of Episiotomy to Perineal Tears in Labor Women - Andriani; Linda Suryani; Eva Santi H. (PT Inovasi Pratama Internasional, 2023)
Episiotomy is a rupture made in the perinea between the vaginal open and the anus to release the baby. Episiotomy is not recommended because it may lead to an increase in the amount of blood lost. The number of events in the field of obstetrics around the world in 2009 accrued 2.7 million cases of perineal rupture wounds in mothers. The purpose of this research was to determine the relationship of episiotomy in labor to the incidence of perineal rupture in the maternal mother at the Ernita maternity clinic. This research is quantitative research with analytical design. The population in this research is all maternal mothers at Ernita maternity hospital as many as 95 people. The sampling technique used in this research is the total population that is sampling from all mother maternity data. The results showed that of 54 people (57%) who performed the episiotomy action in the majority of labor perineal rupture that is as many as 35 people (37%). Chi-square test results there is a relationship between episiotomy in labor to the incidence of perineal rupture in the maternal maternal mother where the p value is 0.040 <0.05. It is desirable for midwives to reduce the action of episiotomy by doing proper labor delivery.